Peningkatan kemampuan HOTS melalui model team games tournament berbasis daring pada siswa SD - Fike Apriliyanti (Universitas Muhammadiyah Malang, 2021)
Pembelajaran tahun 2020/2021 dilaksanakan dengan kegiatan dalam jaringan (daring) dalam pelaksanannya pembelajran memanfaatkan platform online. Kegiatan pembelajaran daring dilaksanakan dengan berbagai model pembelajaran, hal tersebut dilakukan untuk menunjang motivasi siswa dalam mengikuti pembelajaran di kelas. Tujuan utama peningkatan kemampuan HOTS melalui model Team Games Tournament pada siswa SD adalah dapat meningkatkan hasil belajar siswa tersebut. Subjek penelitian ini adalah siswa kelas III C SD Muhammadiyah 04 Batu dengan jumlah dua puluh lima siswa. Model pembelajaran yang digunakan adalah Team Games Tournament (TGT) dengan langkah-langkah sebagai berikut, 1) penyajian materi, 2) kelompok (team), 3) games, 4) tournament , 5) penghargaan tim. Kegiatan pembelajaran yang memuat siklus I dan siklus II. Hasil dari kegiatan penelitian didapat kegiatan belajar selalu meningkat. Persentase kognitif siklus I 70% dan siklus II 92%. Improving HOTS abilities through a courage-based tournament team games model for elementary school students. Learning in 2020/2021 is carried out with activities in the network (online) in the implementation of learning using online platforms. Online learning activities are carried out with various learning models, this is done to support student motivation in participating in classroom learning. The main goal of increasing HOTS abilities through the Team Games Tournament model for elementary students is to improve student learning outcomes. The subjects of this study were twenty-five students of class III C SD Muhammadiyah 04 Batu. The learning model used is the Team Games Tournament (TGT) with the following steps, 1) presentation of material, 2) group (team), 3) games, 4) tournament, 5) team award. Learning activities that contain cycle I and cycle II. The results of research activities show that learning activities are always increasing. The percentage of cognitive cycle I 70% and cycle II 92%.